ShF5H1 overexpression increases syringyl lignin and improves saccharification in sugarcane leaves - Juan Pablo Portilla Llerena; Eduardo Kiyota; Fernanda Raquel Camilo dos Santos; Julio C. Garcia; Rodrigo Faleiro de Lima; Juliana Lischka Sampaio Mayer; Michael dos Santos Brito; Paulo Mazzafera; Silvana Creste; Paula Macedo Nobile (GM Crops & Food)
The agricultural sugarcane residues, bagasse and straws, can be used for second-generation ethanol (2GE) production by the cellulose conversion into glucose (saccharification). However, the lignin content negatively impacts the saccharification process. This polymer is mainly composed of guaiacyl (G), hydroxyphenyl (H), and syringyl (S) units, the latter formed in the ferulate 5-hydroxylase (F5H) branch of the lignin biosynthesis pathway. We have generated transgenic lines overexpressing ShF5H1 under the control of the C4H (cinnamate 4-hydroxylase) rice promoter, which led to a significant increase of up to 160% in the S/G ratio and 63% in the saccharification efficiency in leaves. Nevertheless, the content of lignin was unchanged in this organ. In culms, neither the S/G ratio nor sucrose accumulation was altered, suggesting that ShF5H1 overexpression would not affect first-generation ethanol production. Interestingly, the bagasse showed a significantly higher fiber content. Our results indicate that the tissue-specific manipulation of the biosynthetic branch leading to S unit formation is industrially advantageous and has established a foundation for further studies aiming at refining lignin modifications. Thus, the ShF5H1 overexpression in sugarcane emerges as an efficient strategy to improve 2GE production from straw.